Project-based learning to improve scientific literacy for primary education postgraduate students in science subject - Endang Widi Winarni; Endina Putri Purwandari (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
The research aimed to describe the learning activities and the ability of scientific literacy (attitude, context, knowledge, and competence) Students of Primary Education Postgraduate Program of Bengkulu University in natural science subjects by using the PjBL model. The Classroom Action Research done in three cycles for Primary Education Postgraduate Program students of Bengkulu University in the first semester of 2019/2020 academic year. Instrument and data collection techniques are observations, tests, and rubrics. The observation was on student activities in learning and aspects of caring for the environment and caring for health. The instruments were HOTS test and rubric. The science aspect uses the student report assessment sheet. The indicators of successful actions were the activities of lecturers and students in teaching and learning by using PjBL in good categories, and the percentage of students who show attitudes, context, knowledge, and competencies of science meet good categories at least 80%. The results of this research are the using of Project-Based Learning model can improve the learning activities of Primary Education Postgraduate Program Students of Bengkulu University in a natural science subject and can improve the scientific literacy aspects of an attitude, context, knowledge, and competencies for Primary Education Postgraduate Program in the science subject.